2017
DOI: 10.1101/221168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficiency of nucleotide excision repair explains mutational signature observed in cancer

Abstract: Nucleotide excision repair (NER) is one of the main DNA repair pathways that protect cells against genomic damage. Disruption of this pathway can contribute to the development of cancer and accelerate aging. Tumors deficient in NER are more sensitive to cisplatin treatment. Characterization of the mutational consequences of NER-deficiency may therefore provide important diagnostic opportunities. Here, we analyzed the somatic mutational profiles of adult stem cells (ASCs) from NER-deficient Ercc1-/Δ mice, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…Our analysis of germline and somatic variants in the different pathways where DDRs are involved showed that the Homology Recombination, Fanconi Anemia, and Mismatch Repair pathways are the most affected by both types of mutations, whereas the Nucleotide Excision Repair pathway appears to be more affected by somatic variants in primary tumours than by germline pathogenic variants. The latter finding is in agreement with the results of other authors in that it shows an increased contribution of a somatic mutational pattern 25 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our analysis of germline and somatic variants in the different pathways where DDRs are involved showed that the Homology Recombination, Fanconi Anemia, and Mismatch Repair pathways are the most affected by both types of mutations, whereas the Nucleotide Excision Repair pathway appears to be more affected by somatic variants in primary tumours than by germline pathogenic variants. The latter finding is in agreement with the results of other authors in that it shows an increased contribution of a somatic mutational pattern 25 .…”
Section: Discussionsupporting
confidence: 94%
“…2, panel d). Therefore, our analyses of accumulation of somatic variants in the NER pathway coincide with the results by other authors in that this pathway shows an increased contribution of a somatic mutational pattern (COSMIC mutational signature 8) recurrently observed in various cancer types 25 . So, the disruption of this pathway could potentially drive carcinogenesis and accelerate aging.…”
Section: Ddr Genes Show a Different Pattern Of Accumulation Of Germline And Somatic Variants As A Function Of Protein Lengthsupporting
confidence: 88%
“…Cluster 4 (purple) is dominated by mutation patterns (SBS3 and deletions with microhomology) highly characteristic for homologous recombination deficiency (23). The final cluster (orange) is predominantly characterized by the aging signatures (SBS1, SBS5, and SBS40), although some samples also show APOBEC activity (20,24,25).…”
Section: Organoid Culture Media Composition Functionally Selects For mentioning
confidence: 99%
“…NER pathway is involved in neutralizing oxidative DNA damage [38] and Signature 5 has been also associated with smoking [39], which itself is associated with oxidative damage. Indeed Signature 5 was linked to the NER pathway in a recent study [40].…”
Section: Expression Analysis To Identify Biological Processes Associamentioning
confidence: 94%